Probiotics, Prebiotics, and Synbiotics Improve Uremic, Inflammatory, and Gastrointestinal Symptoms in End-Stage Renal Disease With Dialysis: A Network Meta-Analysis of Randomized Controlled Trials - Yu, Zixian; Zhao, Jin; Qin, Yunlong; Wang, Yuwei; Zhang, Yumeng; Sun, Shiren (Frontiers in Nutrition, 2022)
Background: Probiotics, prebiotics, and synbiotics are three different supplements to treat end stage renal disease (ESRD) patients by targeting gut bacteria. The comprehensive comparison of the effectiveness of different supplements are lacking. Objectives: The purpose of this network meta-analysis (NMA) is to assess and rank the efficacy of probiotics, prebiotics, and synbiotics on inflammatory factors, uremic toxins, and gastrointestinal symptoms (GI symptoms) in ESRD patients undergoing dialysis. Methods：Randomized clinical trials were searched from the PubMed, Embase, and Cochrane Register of Controlled Trials databases, from their inception until September 4, 2021. Random-effect model were used to obtain all estimated outcomes in network meta-analysis (NMA). Effect estimates were presented as mean differences (Mean±SD) with 95% confidence interval (CI). The comprehensive effects of all treatments were ranked by the surface under the cumulative ranking (SUCRA) probabilities. Results: Twenty-five studies involved 1106 participants were included. Prebiotics were superior in decreasing Interleukin-6 (IL-6; SMD -0.74, 95% CI [-1.32, -0.16]) and tumor-necrosis factor-α (TNF-α; SMD -0.59, 95% CI [-1.09, -0.08]), synbiotics were more effective in declining C-reactive protein (CRP; SMD -0.69, 95% CI [-1.14, -0.24]) and endotoxin (SMD -0.83, 95% CI [-1.38, -0.27]). Regarding uremic toxins, prebiotics ranked highest in reducing indoxyl sulfate (IS; SMD -0.43, 95% CI [-0.81, -0.05]), blood urea nitrogen (BUN; SMD -0.42, 95% CI [-0.78, -0.06]), and malondialdehyde (MDA; SMD -1.88, 95% CI [-3.02, -0.75]). Probiotics were rated as best in alleviating GI symptoms (SMD: -0.52, 95% CI [-0.93, -0.1]). Conclusions: Our research indicated prebiotics were more effective in declining IL-6, TNF-α, IS, MDA, and BUN, synbiotics lowering CRP and endotoxin significantly, and probiotics were beneficial for alleviating GI symptoms, which may contribute to better clinical decisions. This study was registered in PROSPERO (Number: CRD42021277056).